Analysis of tripartite Synaptotagmin‐1‐SNARE‐complexin‐1 complexes in solution - Klaudia Jaczynska; Luis Esquivies; Richard A. Pfuetzner; Baris Alten; Kyle D. Brewer; Qiangjun Zhou; Ege T. Kavalali; Axel T. Brunger; Josep Rizo (FEBS Open Bio, 2023)
Characterizing interactions of Synaptotagmin‐1 with the SNARE complex is crucial to understand the mechanism of neurotransmitter release. X‐ray crystallography revealed how the Synaptotagmin‐1 C2B domain binds to the SNARE complex through a so‐called primary interface and to a complexin‐1‐SNARE complex through a so‐called tripartite interface. Mutagenesis and electrophysiology supported the functional relevance of both interfaces, and extensive additional data validated the primary interface. However, ITC evidence suggesting that binding via the tripartite interface occurs in solution was called into question by subsequent NMR data. Here, we describe joint efforts to address this apparent contradiction. Using the same ITC approach with the same C2B domain mutant used previously (C2BKA‐Q) but including ion exchange chromatography to purify it, which is crucial to remove polyacidic contaminants, we were unable to observe the substantial endothermic ITC signal that was previously attributed to binding of this mutant to the complexin‐1‐SNARE complex through the tripartite interface. We were also unable to detect substantial populations of the tripartite interface in NMR analyses of the ITC samples or in measurements of paramagnetic relaxation effects, despite the high sensitivity of this method to detect weak protein complexes. However, these experiments do not rule out the possibility of very low affinity (KD > 1 mm) binding through this interface. These results emphasize the need to develop methods to characterize the structure of synaptotagmin‐1‐SNARE complexes between two membranes and to perform further structure–function analyses to establish the physiological relevance of the tripartite interface.